THE EFFECT OF MUZARA'AH CONTRACT ON WELFARE LEVEL OF POTATO FARMERS (Case Study in Permata District, Bener Meriah Regency) - Ichsan Ichsan; Hanif Hanif; Andika Mursada (Faculty of Economics and Business, Universitas Malikussaleh, 2022)
The purpose of this study is to analyze the effect of the muzara'ah contract on the welfare level of potato farmers in the Permata District, Bener Meriah Regency. The data used in this study are primary data by distributing questionnaires to 85 respondents who were used as research samples. Data processing is done with the help of a simple linear regression equation model. The results showed that the muzara'ah contract had a significant effect on the welfare level of potato farmers in the Permata District, Bener Regency with a tcount of 3.297 and a significant level of 0.001. The muzara'ah contract has a strong relationship with the welfare level of potato farmers in the Permata District, Bener Meriah Regency. This can be seen from the correlation coefficient (R) of 0.740 (74%). The muzara'ah contract has the ability to explain its effect on the welfare level of potato farmers in the Permata District, Bener Meriah Regency by 71.6%. The remaining 38.4% is influenced by other variables outside this research model, such as labor, work experience, length of business, number of dependents, product quality, and others.